Analysis of Service Response Time in the Emergency Department (ED) of Grandmed Hospital - Ayu Siti Chadijah Nasution; Rahmadani Sitepu; Novita Br Ginting Munthe (JURNAL KESMAS DAN GIZI (JKG), 2026)
The Emergency Department (ED) serves as the frontline of hospital services and requires a rapid response time to ensure patient safety. This study aimed to analyze the service response time in the Emergency Department of Grandmed Hospital Lubuk Pakam in 2025, as well as the factors influencing it. This research employed a quantitative analytic observational method with a cross-sectional approach. The sample consisted of 97 respondents selected using a consecutive sampling technique from the population of ED patients in 2025. Data were obtained from medical records and hospital information systems and analyzed using univariate, bivariate, and multivariate methods. The results showed that triage category (p = 0.001), compliance with response time standards (p = 0.000), number of medical personnel (p = 0.003), availability of treatment rooms (p = 0.002), and patient arrival time (p = 0.004) had a significant effect on service response time. Multivariate analysis indicated that compliance with response time standards was the most dominant factor, with an odds ratio (OR) of 5.21 (95% CI: 2.10–12.95; p = 0.000).In conclusion, service response time is influenced by patient-related factors, human resources, infrastructure, and service management systems. Therefore, it is recommended to improve compliance with response time standards, optimize the number of medical personnel, and enhance ED management to improve service quality and patient safety.